Shear problem of T-sectional composite reinforced concrete beams - Jabłoński, Łukasz (Budownictwo i Architektura / Civil and Architectural Engineering, 2011)
The article presents data available in the literature concerning shear problem of composite concrete T-beams - their running in support zone and contact surface. To begin with presented where are in the civil engineering T-sectional composite elements. Following made an analysis of method for geometric buckling (according to standards [12,14]) T-sections of monolithic and composite beams without and with cracked contact surfaces. There were also literature [6,7,8,9] and standards [12,13] studies in field of support zone and between flange and web shearing solid T-beams in order to know the matter. In the essence of problem concentrated on: horizontal shearing in contact surface between precast and cast in place components, running support zone of bending composite beams and complete rib-and-slab floors’ sharing data [3,5,12,14,15,16]. At the end reported the most important researches in shearing and running contact surface of composite T-beams [3,4,10,11] also draw a conclusions to my own work.